Genital syringocystadenocarcinoma papilliferum: An unusual location and review of the literature - Mohammad Shahidi Dadras (Elsevier, 2022)
Syringocystadenocarcinoma papilliferum (SCACP) is an extremely rare adnexal neoplasm of the sweat glands. It is believed to arise from the malignant transformation of syringocystadenoma papilliferum (SCAP). The majority of cases present on the head and neck and up to 17% of cases show metastatic progression. These tumors seldom occur in the anogenital area and, to date, only one case has been reported on the penis. Here, we report a rare case of SCACP in a 65-year-old man who presented with an erythematous, non-healing, ulcerated lesion on the penis.